Pembuatan Sistem Informasi Toko Komputer - Marpaung, Noveri Lysbetti; Hutabarat, Sakti; Maulana, Farhan (FORDICATE, 2022)
Nowadays, Computer/Laptop Store is so needed by society, which majority are employees and students. All them use computer/laptop to do their activities. Establishment of Information System is carried out in company of Garuda Cyber Indonesia. Th Information System Design is created to be a new idea for Garuda Cyber Indonesia Company in creating a Computer Store Information System, which is very suitable for companies engaged in Technology and Information field. To design this Information System, PHP is used as main programming language and framework of Codeigniter 3 as well. By using this Computer Store Information System, hopefully, it can help owners of computer shop, especially for conventional computer shop. By this Information System, the owner can spread information of his/herstores and reach customers from any where and any time. Through this Information System, customers can get information easier about sold computer/laptop from this store.